Interest Rate Volatility and Asymmetric Interest Rate Pass-through in Selected SAARC Countries - Sim, Chong Yang (Universiti Malaysia Sarawak, (UNIMAS), 2020)
The outbreak of the Global Financial Crisis in 2008 witnessed the success of monetary policy in stabilising the economy. Central banks have been actively using different monetary policy strategies to achieve and maintain desirable economic goals, such as low unemployment levels, stable general price levels etc. Central banks usually convey monetary policy decisions by firstly adjusting policy rates that subsequently passed-through to bank retail rates, in which the latter process is known as interest rate pass-through, before the monetary policy decisions are finally channelled to the economy through various monetary policy transmission channels. Previous literature has also discovered that interest rate volatility influences bank retail rate adjustment behaviour, while changes in the monetary stance also affect the bank retail rate volatility. Therefore, this study intends to examine the pass-through mechanism in four major SAARC countries, namely; Pakistan, India, Bangladesh and Sri Lanka. This study used the Threshold Autoregressive and Momentum Threshold Autoregressive models of Enders and Siklos (2001) and the Error Correction Exponential Generalised Autoregressive Conditional Heteroscedasticity in Mean (EC-EGARCH-M) model proposed by Wang and Lee (2009). Based on the empirical results, the first stage of the interest rate pass-through mechanism is complete in Pakistan, India and Sri Lanka only. While, the second stage of the interest rate pass-through mechanism is incomplete for both the deposit rate and lending rate models of all of the sample countries, except for the lending rate model of Sri Lanka. The money market rates and bank retail rates of all of the sample countries are found to have asymmetric long-run relationships, except for the lending rate of India. It has also been discovered that the asymmetric short-run adjustment between the money market rates and bank retail rates of Pakistan and Sri Lanka and between the money market rates and deposit rate of India supported the adverse customer reaction hypothesis, while Bangladesh supported the collusive pricing behaviour hypothesis. In terms of the effect of interest rate volatility on the adjustment behaviour of bank retail rates, it is significantly positive for both bank retail rate models of Pakistan and the lending rate model of Bangladesh, while significantly negative for the deposit rate model of Bangladesh. Its effect is insignificant on both retail rate models of India and Sri Lanka. As for the presence of asymmetry in the conditional volatility of both bank retail models, the asymmetry effect is found for the lending rate model of all of the sample countries, while the leverage effect is found on the deposit rate model of Pakistan and Sri Lanka. Generally, this study has managed to achieve its objectives. Various relevant policy recommendations are proposed to the central banks of the sample countries to improve the performance of interest rate passthrough in their countries.